Categorizing and characterizing intestinal dysbiosis: evaluating stool microbial test clinical utility - Oliver, Lia; Malagón, Marta; Ramió-Pujol, Sara; Sánchez-Vizcaino, Mireia; Sánchez-Algans, Roser; Lacosta, Eva; Saéz-Zafra, Marc; Serra-Pagès, Mariona; Aldeguer, Xavier; Garcia-Gil, Jesús; Oduber, Sara (Frontiers in Microbiomes, 2025)
BackgroundInterest in the intestinal microbiota has surged in recent years, leading to the development of various microbiota tests utilizing stool analysis. This study aimed to assess the clinical utility of the TestUrGut.ResultsThe abundances of different microbial markers analyzed correlated with various factors and symptoms. While no age differences were observed, an increase in A. muciniphila abundance was noted in women compared to men. Body mass index significantly influenced the abundance of A. muciniphila and M. smithii. Additionally, variations in the abundances of A. muciniphila and M. smithii, as well as a greater presence of Firmicutes or Bacteroidetes based on stool patterns, were linked to diarrhea or constipation. The dysbiosis index was validated, distinguishing between temporary and pathological dysbiosis.ConclusionsThis study revealed significant relationships between the intestinal microbiota and digestive tract symptoms. Microbial markers have emerged as robust indicators of the overall state of the intestinal microbiota, demonstrating that variations are closely associated with patients’ clinical symptoms.